A Different Approach To Family Involvement - Leslie Patterson; Shelia Baldwin; Rubén Gonzales; Irma Guadarrama; Liz Keith (Networks: An Online Journal for Teacher Research, 1999)
The Houston Chronicle recently quoted a school counselor who blamed low student achievement on parents, whom he called "a bunch of seventh-grade dropouts who can't add 2 plus 2" (Houston Chronicle, 1998, p. 21A). As educators, we see too many of our colleagues play that blame game as we try to respond to increasing public pressure to make schools "work." The logic goes something like this: "We are doing everything we know how, and these children still are not succeeding. If only their parents would (fill in the blank), everything would be just fine."